Multicentre open-label randomised controlled trial comparing the efficacy and safety of colistin-based combination therapy with the best available therapy for treating hospital-acquired pneumonia or bloodstream infections caused by carbapenem-resistant Enterobacteriaceae (COUNT-CRE): a study protocol - Tao Chen; Chen Zhang; Jianfeng Xie; Yingzi Huang; Xiangquan Li; Jiaqiong Li (BMJ Open, 2025)
Introduction The prevalence of carbapenem-resistant Enterobacteriaceae (CRE) infections is increasing worldwide. However, the evidence regarding the treatment of infections caused by CRE is either low or conditional.Methods and analysis This multicentre, investigator-initiated, open-label, randomised controlled, non-inferiority trial compares colistin-based combination therapy with the best available therapy for treating CRE infections. This study is being conducted at 15 centres in China. We include participants with hospital-acquired pneumonia (HAP) or bloodstream infections (BSI) caused by CRE. Participants will be randomly assigned to a colistin-based combination therapy group or the best available therapy group. The primary outcome is the 14-day all-cause mortality. Secondary outcomes include 14-day clinical cure rate, 14-day efficacy rate, intensive care unit (ICU)-free days within 28 days after randomisation, 14-day microbiological cure rate, incidence of adverse events (AEs) and serious AEs within the first 28 days, hospital mortality, 28-day all-cause mortality and ICU mortality. A target sample size of 404, with 322 evaluable patients (161 in each group) allowed for at least 80% power (one-sided significance level of 0.025), assuming a 15% non-inferiority margin and a 14-day all-cause mortality rate of 35% in both groups. Primary outcome will be assessed based on the microbiologically modified intent-to-treat, and one interim analysis is planned when 50% of the participants have been enrolled.Ethics and dissemination The study was approved by the Research Ethics Boards at Zhongda Hospital (file number: 2023ZDSYLL295-P03) and all participating centres. Informed consent will be obtained from all participants. The trial will be conducted under the oversight of an independent data and safety monitoring committee. Results will be disseminated in peer-reviewed journals.Trial registration number NCT06051513.